C3 glomerulopathy: a rare kidney histological presentation of multiple myeloma - Costa,Joana Silva (2018)
C3 Glomerulopathy is a rare disease caused by abnormal control of the alternative complement pathway, resulting in a predominant glomerular C3 deposition. Its association with multiple myeloma has been reported in recent literature. We present a case of a 66-year-old women, referred for a nephrology consultation with a stage 4 chronic kidney disease, microhematuria, leukocyturia, sub-nephrotic range proteinuria (1.3 g/24hours), albumin 3.7 g/dl and dyslipidemia. She had been previously studied in a Hematology consultation for a normocytic anemia and an IgG Kappa monoclonal gammopathy, with 16% of plasma cells in bone marrow aspiration, but no hypercalcemia or lytic bone lesions. Autoimmune tests (ANCA, ANA, Anti-dsDNA antibody), C3 and C4 were negative. Eight months later, the patient complained of hypertension and edema, and presented a mild decrease in serum C3 (0.86 g/L [0.90-1.80]) and progressive nephrotic proteinuria (from 4.5 to 6.1 g/24h), with hypoalbuminemia. A kidney biopsy was performed, and we found mild chronic non-specific glomerular and tubule-interstitial findings, on light microscopy, and mesangial C3 deposits (+++), without immunoglobulin deposits, on immunofluorescence. Immunofluorescence with protease-digested paraffin sections was also negative. Genetic study found no complement gene mutation. She was treated with prednisone 1mg/Kg/day, with a favorable clinical and laboratorial response, but whether this treatment is enough it is still being pondered between nephrologists and hematologists